Roles of Perceived Motivational Climates Created by Coach, Peer, and Parent on Dispositional Flow in Young Athletes - AŞÇI, FEVZİYE HÜLYA (SAGE PUBLICATIONS INC, 2017)
We investigated the contribution of perceived motivational climates created by coach, peer, and parent on the dispositional flow experience of young athletes. Eighty-six female (M-age=14.24, SD=1.38 years) and 134 male (M-age=16.28, SD=1.17 years) athletes completed questionnaires of perceived motivational climates created by coach, peer, and parent and the Dispositional Flow Scale-2. Results of hierarchical multiple regression analyses indicated that perceived task-involving coach (=.40, p<.001) and peer (=.28, p<.002) motivational climates were the only significant predictors of dispositional flow. These findings suggest that task-involving motivational climates should be strengthened to increase experience of flow.
Keywords: motivational climate; dispositional flow; young athlete; task-involving motivational climate; peer-created motivational climate; INTRINSIC MOTIVATION; GOAL ORIENTATIONS; PHYSICAL-EDUCATION; YOUTH SPORT; NEED SATISFACTION; ACHIEVEMENT GOAL; TASK INVOLVEMENT; ELITE SPORT; PERCEPTIONS; PARTICIPANTS